Konstruksi Moderasi Beragama dalam Gerakan Jamaah Tablig Kota Palopo - Andi Asraf; Baso Hasyim; Muhammad Ilham (Bayt Al Hikmah: Jurnal Pendidikan dan Pengembangan Masyarakat Islam, 2025)
The urgency of this research lies in understanding how the construction of religious moderation is formed within the Jamaah Tabligh movement in Palopo City, considering the importance of moderation in maintaining religious harmony in a pluralistic society. This study explores the perceptions of the Jamaah Tabligh movement regarding the concept of religious moderation and its implications for their da'wah (Islamic preaching) activities. The research employs a descriptive qualitative method using an ethnographic approach. Data were collected through observation, interviews, and documentation, and then analyzed through description, analysis, and interpretation. The findings reveal that most members of the Jamaah Tabligh had never heard of the term "religious moderation," primarily due to a lack of literacy and socialization related to the concept. Some informants even encountered the term for the first time during interviews with the researcher. Nevertheless, the majority of Jamaah Tabligh members expressed agreement and support for the principles of religious moderation as defined by the Ministry of Religious Affairs. Although most members are unfamiliar with the term itself, the values of religious moderation are implicitly reflected in their activities. The da'wah practices of the Jamaah Tabligh in Palopo City indicate a form of moderate religious expression.